Exploring trade-offs between development and conservation outcomes in Northern Cambodia. (February 2018) - Beauchamp, Emilie; Clements, Tom; Milner-Gulland, E.J.
Highlights: Spatial correlates of Economic Land Concession (ELC) placement and deforestation in northern Cambodia are modelled. ELC placement does not respond to implementation criteria stated in policy documents. Deforestation is more likely to occur in ELCs, and less likely in managed protected areas. Results point to discrepancies in the implementation of the Land Law. Development impacts may compromise long-term environmental sustainability. Abstract: Trade-offs between different land use outcomes are inevitable to meet both development and conservation agendas, especially in developing countries where aspirations for development take place within the world's most biodiversity-rich areas. Reports at the national or subnational levels about how trade-offs between conservation and development outcomes materialise once implemented are limited and regionalized analyses are required to understand how they materialise spatially once policies are executed. We take the case study of northern Cambodia, where both protected areas (PAs), as a conservation policy, and Economic Land Concessions (ELCs), as a developmental agricultural intensification strategy, have been implemented. We explore the influences on placement of ELCs and the extent to which they overlap with protected areas, using mixed effect models. We then determine the predictors of deforestation in the study area between 2008 and 2013, including presence of ELCs and PAs. ELC placement does not respond to expected socio-environmental factors related to implementation criteria in policy documents, and is not influenced by the presence of PAs. ELCs represent the most significant driver of deforestation of the factors considered. PAs limit deforestation but only if well-managed. This failure to achieve the balanced trade-off between conservation and development outcomes which policies intend points to development impacts compromising environmental sustainability in the long-run.